The Influence of Process Parameters on Non-Conventional Technology in Drawing Cassette Roller Die (Part 1). (2016) - Mihu, Adriana-Maria; Sas-Boca, Ioana Monica; Marian, Ionuţ; Iluţiu-Varvara, Dana-Adriana; Nistor, Liviu
Abstract: This paper presents a new approach to the influence of the process parameters on non-conventional technology for drawing in cassette roller die. This technology combines two conventional methods of plastic deformation. The rolling, in this method the wire is passed through the two pairs of roller and, the drawing, using the drawing force that exist at the exit of the wire between the rolls. In conclusion there are two forces involved in the process of plastic deformation: drawing force and rolling force. It has been shown that these forces are strongly influenced by variation of certain process parameters such as: the initial diameter of the sample, the elongation coefficient, the contact surface roll/sample, the average pressure of rolling, the friction coefficient and the rollers working radius. The results depicts a helpful insight into the effects of the process parameters in the wire drawing with cassette roller die, thus furnishing the basic guidelines for process design and optimization.